Provision of services to asylum seekers. Are there lessons from the experience with Kosovan refugees?. Issue 3 (1st March 2002) - Ghebrehewet, S; Regan, M; Benons, L; Knowles, J
Abstract : Arrangements that were made to receive and support Kosovan refugees in the United Kingdom should be applied to asylum seekers arriving in the country.